Hong Kong : culture and the politics of disappearance - Abbas, M. A. (M. Ackbar) (Public worlds, 1997)
In an intriguing and provocative exploration of its cinema, architecture, photography, and literature, Ackbar Abbas considers what Hong Kong can teach us about the future of both the colonial city and the global city.